(untitled) (Global Journal of Human-Social Science, 2019)
The world competitive sports games, showing a very competitive situation, the winner will have to participate in the support behind is a high level of theory and technology, more discipline involved in training to improve the effect of training quality, plate training theory involves the track and field, swimming weightlifting project, through access to relevant data, USES the analogy analysis method; According to the research and analysis results, there are still differences in the plate training structure of jumping project training, and there are obvious gaps in the application of training theory and practice. Therefore, the training plan is not specific and specific. The research conclusion of this paper argues that the theory of sports training needs to be updated and improved to meet the needs of the intensity of modern sports competition. Multidisciplinary evaluation data and multidimensional structure are used to formulate medium -and long-term training plans to guide jumping training for athletes to achieve excellent results.